Evaluation of Complete Blood Count Indices (NLR, PLR, MPV/PLT, and PLCRi) in Healthy Dogs, Dogs With Periodontitis, and Dogs With Oropharyngeal Tumors as Potential Biomarkers of Systemic Inflammatory Response. (December 2017) - Rejec, Ana; Butinar, Janos; Gawor, Jerzy; Petelin, Milan
The aim of the study was to retrospectively assess complete blood count (CBC) indices of dogs with periodontitis (PD; n = 73) and dogs with oropharyngeal tumors (OT; n = 92) in comparison to CBC indices of healthy dogs (HD; n = 71). Neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio, mean platelet volume to platelet ratio, and platelet large cell ratio index (PLCRi) were evaluated as biomarkers of systemic inflammatory response provoked by PD and OT. Results of multivariable polytomous logistic regression analysis indicated no significant associations between CBC indices and PD. Both NLR and PLCRi were significantly higher in dogs with OT when compared to HD and dogs with PD and could, therefore, indicate a tumor-associated systemic inflammatory response. Additional studies of CBC indices, along with other biomarkers of systemic inflammatory response, are recommended to validate them as reliable indicators of clinical disease activity.